An Evaluation of Disability Rights Implementation in Indonesian Correctional Institutions: The Cases of LPKA (Youth Correctional Center) Tomohon and Pematang Siantar - Suparman Marzuki; Despan Heryansyah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The fulfillment of the rights of persons with disabilities has received growing attention, particularly following the enactment of Indonesia’s Law on Persons with Disabilities. In correctional settings, the Directorate General of Corrections mandated in 2020 that all Correctional Technical Implementation Units establish Disability Service Units (Unit Layanan Disabilitas/ULD) to ensure adequate reasonable accommodation for inmates with disabilities. After four years of implementation, it is necessary to evaluate how effectively these units have operated. This study aims to analyze the implementation of ULD policies in ensuring reasonable accommodation and to identify the challenges encountered in fulfilling disability rights within correctional environments. To narrow the scope, the research focuses on two institutions: LPKA Tomohon and Pematang Siantar Prison. The research employs a qualitative approach, gathering primary data through in-depth interviews and direct observation, and is supported by secondary sources from literature reviews, academic articles, books, and relevant research reports. The findings indicate that both institutions have adopted various measures, particularly to improve infrastructure and strengthen the capacity of ULD officers. However, significant challenges remain, including limited policy and budgetary support, constraints on institutional leadership capacity, and varying availability of civil society organizations across regions. These factors hinder ULDs from functioning optimally to provide accessible and inclusive correctional services. Overall, this study underscores the need for institutional strengthening and more comprehensive support to ensure that Disability Service Units can effectively safeguard the rights of persons with disabilities within correctional settings.